Fitossociologia e paisagismo: identificação de espécies arbóreas para uso na arborização urbana - Aguiar, Roberto Valmorbida de (2017)
The arboreal vegetation in a city has besides ornamental function, a series of environmental regulations, such as controlling the humidity of the atmosphere, filtering the pollution, regulating the atmospheric air and the temperature of the urban environment. Although Brazil is recognized as one of the most biodiverse countries on the planet, possessing the largest number of tree species, the urban ecosystem presents a large number of exotic trees in the streets, with few native species being used in urban landscape design. The application of phytosociology in forest surveys as a strategy for the conservation of the flora of a community is relatively common, but the use of its results to indicate native species of a region for use in urban afforestation presents as a new possibility of the applicability of this technique. Thus, the objective of the study was to identify the forest formation of a subtropical forest fragment and to use the results to indicate which tree species of the study have ornamental potential for use in urban landscaping, in addition to correlating soil variables with the abundance and distribution of the species.The study area is located in the southern Brazil, being a municipal conservation unit called “Parque N atural Municipal de Sertão” (28°02'31 "S, 52°13'28" W) with 500 ha, belonging to the Atlantic Forest. The methodology used was the plots method, with 100 sample units of 10 x 10m divided into three areas with different ecological characteristics, totaling 10.000 m 2of sampled area. All individuals with PAP (chest circumference) ≥ 15 cm were identified and measured. The differences between the three areas were verified through an analysis of variance (ANOVA). The soil chemical analysis was performed in 10 plots, where Pearson Correlation Coefficient was used to correlate species with more than five individuals with soil chemical variables. A cluster analysis was also carried out, between the main species of the survey and its characteristics for use in urban afforestation, as well as a main component analysis (PCA) with the purpose of evidencing the factors responsible for the groupings. A total of 83 tree species belonging to 33 botanical families were identified in a total of 1537 individuals, confirming the Araucaria Forest as the local forest formation. Potassium showed correlation whith three in the sample units studied. The study pointed out that species with the highest values of importance found in the phytosociological survey are also the most suitable for use in urban afforestation in the regions with the same forest formation. These species belong to the ecological group of pioneers and secondary, presenting the form of growth and tolerance light suitable for use in urban ecosystems. In addition to the ecological group, the flowering season and the size of the species indicated by the PCA were the most important characteristics for the indication of the species